A Simple Approach Assessing the Vegetable Content of Asian Takeout Meals with Nutrition Education Potential - Pollard, Christina; Kerr, Deborah; Edwards, Elizabeth; McNab, Katherine; Scott, Natalie; Begley, Andrea (Scientific Research Publishing Inc, 2012)
A demand for convenient eating options has led to an increase in foods eaten away from home, and consumers are looking for healthy options when they eat out. Increasing vegetable consumption is a key public health nutrition prior-ity. Although Asian menu items are considered a healthy option, there is little information about their relative health-fulness. This study aims to pilot a simple method for measuring the vegetable content of popular Asian dishes for use in nutrition education. Thirty vegetable containing take-out dishes from three Asian restaurants (Chinese, Thai and Singaporean) in Perth, Western Australia were photographed and weighted with, and without the vegetables. Standard 75 gram vegetable servings per dish and the average vegetable content between cuisines were compared. The mean vegetables servings per dish was 1.8 (0.25 to 5.5) with no statistical difference between cuisines (p > 0.05). The variety and amount of vegetables in individual dishes varied within each cuisine. Vegetarian dishes had the highest vegetable content and noodle and rice dishes the lowest (0.23 - 0.75 servings/dish). Digital imagery clearly, simply and quickly displayed the vegetable content of Asian dishes. The Asian take-out dishes were low in vegetables. Nutrition educators should encourage Asian food businesses to increase the vegetable content of their menus and advise customers to choose at least one vegetarian dish.